Structure and Gating Dynamics of Na+/Cl– Coupled Neurotransmitter Transporters - Joseph, Deepthi; Pidathala, Shabareesh; Mallela, Aditya Kumar; Penmatsa, Aravind (Frontiers in Molecular Biosciences, 2019)
Neurotransmitters released at the neural synapse through vesicle exocytosis are spatiotemporally controlled by the action of neurotransmitter transporters. Integral membrane proteins of the solute carrier 6 (SLC6) family are involved in the sodium and chloride coupled uptake of biogenic amine neurotransmitters including dopamine, serotonin, noradrenaline and inhibitory neurotransmitters including glycine and γ-amino butyric acid. This ion-coupled symport works through a well-orchestrated gating of substrate through alternating-access, which is mediated through movements of helices that resemble a rocking-bundle. A large array of commercially prescribed drugs and psychostimulants selectively target neurotransmitter transporters thereby modulating their levels in the synaptic space. Drug-induced changes in the synaptic neurotransmitter levels can be used to treat depression or neuropathic pain whereas in some instances prolonged usage can lead to habituation. Earlier structural studies of bacterial neurotransmitter transporter homologue LeuT and recent structure elucidation of the Drosophila dopamine transporter (dDAT) and human serotonin transporter (hSERT) have yielded a wealth of information in understanding the transport and inhibition mechanism of neurotransmitter transporters. Computational studies based on the structures of dDAT and hSERT have shed light on the dynamics of varied components of these molecular gates in affecting the uphill transport of neurotransmitters. This review seeks to address structural dynamics of neurotransmitter transporters at the extracellular and intracellular gates and the effect of inhibitors on the ligand-binding pocket. We also delve into the effect of additional factors including lipids and cytosolic domains that influence the translocation of neurotransmitters across the membrane.